ANALYSIS OF ELEMENTARY SCHOOL STUDENTS DIFFICULTIES’ IN SOLVING INTEGER WORD PROBLEMS - Chusnul Ainia; Mohammad Faizal Amir (MaPan : Jurnal Matematika dan Pembelajaran, 2021)
This type of research is descriptive qualitative with a case study approach. This study aimed to identify forms of students’ conceptual and principle difficulties in solving integer story problems. The research participants were 34 fifth-grade elementary students. The purposive sampling technique was used to select research subjects based on the minimum completeness criteria value. Methods of data collection using tests and interviews. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The results showed that there were two types of difficulties for elementary school students in solving integer story problems, namely, conceptual difficulties and principle difficulties. The form of conceptual difficulties experienced by students is the difficulty in converting story problems into mathematical form. Besides that, students tend not to write down the steps according to solving story problems, and the principal difficulties experienced by students include errors in performing mathematical calculations. This can be minimized by increasing practice questions in the form of story problems.